Metal(loid)s in superficial sediments from coral reefs of French Polynesia. (June 2020) - Besson, Marc; Metian, Marc; Bustamante, Paco; Hédouin, Laetitia
Abstract: French Polynesia exhibits a wide diversity of islands and coral-reef habitats, from urbanized high islands to remote atolls. Here, we present a geographically extensive baseline survey that examine the concentrations of nine metals (Ag, Cd, Co, Cu, Fe, Mn, Ni, Pb and Zn) and one metalloid (As) in superficial sediments from 28 sites spread over three islands of French Polynesia. We used Principal Component Analysis, Pearson's correlation, hierarchical cluster analysis and generalized linear mixed-effect models on Pollution Load Index to investigate site contamination and metal(loid) associations. At most sites, metal(loid) concentrations were below commonly applied sediment quality guidelines. However, a few sites located near farming activities, river discharges and urbanized areas showed concentrations above these guidelines. This study provides critical baseline values for metal(loid) contaminants in this region and in coral-reef areas in general, and spur decreased discharge of metal(loid) contaminants in the anthropogenised areas of French Polynesia. Highlights: Baseline of metal(loid)s in sediments from French Polynesia (28 sites; 3 islands). Sediment Quality Guidelines were exceeded for at least one element at 17 sites. Levels at remote sites were lower than most previous records in tropical reef areas.